Energy-agriculture nexus: Exploring the future of artificial intelligence applications - Kabir, Masud; Ekici, Sami (Elsevier, 2024)
Energy and agriculture are two independent sectors that share a mutual coexistence referred to as the energyagriculture nexus. In an attempt to facilitate the capacity of this coexistence simultaneously, there is a need for involvement of latest technologies such as the artificial intelligence (AI). This research focused on the incorporation of AI along the energy-agriculture nexus, in an attempt to explore the applications, opportunities, challenges and its potential implications for various stakeholders. According to an intensive literature survey conducted, AI applications were found to be on a significant rise since the last decade, specifically in prediction applications and optimization applications, respectively, with research literature focusing mainly on bioenergy (55%), energy use analysis (17%), process value chain (6%), energy-efficient irrigation (6%), energy in greenhouse (6%), livestock management (2%), farm power and machinery (4%) and risk management (4%). Challenges observed in the literature were observed in terms of data availability, data complexity and heterogeneity, computing power, accountability and transparency in decision-making and research focus. In order to fully comprehend the implications of AI integration along the energy-agriculture nexus and to develop strategies and guidelines for maximizing the advantages of this technology while minimizing potential risks and adverse effects on stakeholders, future research works were discussed.
Keywords: Energy -agriculture nexus; Artificial intelligence; Applied AI; Energy; Agriculture